Postactivation potentiation attenuates resistance exercise performance decrements following aerobic exercise in trained men - Conrado De Freitas, Marcelo [UNESP] (2020)
BACKGROUND: The purpose of this study was to investigate if a post-activation potentiation (PAP) protocol may attenuate the acute interference induced by high-intensity intermittent exercise (HIIE) and on subsequent strength exercise performance in recreationally trained men. METHODS: Eleven resistance-trained men (age: 25.7±3.7 y) randomly completed three experimental trials: strength exercise (SE) only (4 sets of maximal number of repetitions at 70% on the 45° leg press); concurrent exercise (CE) comprised 5000-m of HIIEat maximal aerobic speed (1:1 effort and pause ratio) followed by SEprotocol; CE with post-activation potentiation (CE-PAP), comprised the same CEprotocol preceded by one set of 2 repetitions at 90% of 1RM on the 45° leg-press before strength exercise. The number of repetitions performed was recorded for each set and total weight lifted was calculated. RESULTS: The CEcondition induced a greater decrement in volume for the leg press compared to SE and CE-PAP in sets 1 (24±21%; 18±25%), 2 (20±21%; 22±22%), and 3 (19±20%; 25±15%), respectively. Total weight lifted was greater after SE(8,795±2,581 kg) and CE-PAP(8.809±2.655 kg) conditions compared to CE(7.049±2.822 kg) (SEvs. CE: P=0.020) and (CE-PAP vs. CE: P=0.010) but there was no significant difference between SE and CE-PAP(P=1.00). CONCLUSIONS: PAP using a heavy load attenuated acute interference (total volume during lower-body strength) generated by HIIEprotocol, but did not enhance volume compared to SEalone.